The emergence and proliferation of agroholdings and mega farms in a global context - Hermans, Frans L. P. (2017)
Fil: Hermans, Frans L. P. Leibniz Institute of Agricultural Development in Transition Economies (IAMO). Department Structural Change. Halle (Saale), Germany.